Redox-Active Ligand-Induced Homolytic Bond Activation - Broere, Daniël L. J.; Metz, Lotte L.; de Bruin, Bas; Reek, Joost N. H.; Siegler, Maxime A.; van der Vlugt, Jarl Ivar (Angewandte Chemie International Edition, 2015)
Coordination of the novel redox‐active phosphine‐appended aminophenol pincer ligand (PNOH2) to PdII generates a paramagnetic complex with a persistent ligand‐centered radical. The complex undergoes fully reversible single‐electron oxidation and reduction. Homolytic bond activation of diphenyldisulfide by the single‐electron reduced species leads to a ligand‐based mixed‐valent dinuclear palladium complex with a single bridging thiolate ligand. Mechanistic investigations support an unprecedented intramolecular ligand‐to‐disulfide single‐electron transfer process to induce homolytic SS cleavage, thereby releasing a thiyl (sulfanyl) radical. This could be a new strategy for small‐molecule bond activation. PNO duet: The redox‐active pincer ligand PNO, which has a flanking phosphine group, can coordinate to PdII in various oxidation states. One‐electron reduction from paramagnetic [PdCl(PNO)] generates a competent reagent for the homolytic bond activation of disulfides through ligand‐to‐substrate single‐electron transfer. The resulting dinuclear Pd species, which has a monothiolate bridgehead, shows well‐defined ligand mixed valency in the solid state.